EVALUATION OF ADHERENCE AND INSULIN INJECTION PRACTICES IN PEOPLE WITH TYPE II DIABETES MELLITUS - Mario Esau Katuuk; Gresty Natalia Maria Masi; Muhamad Nurmansyah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
The practice of insulin injection in people with Diabetes Mellitus must be carried out appropriately and obediently by the patient for optimal regulation of glycemic control, preventing complications, and improving quality of life. This study was conducted to identify the description of insulin injection adherence and insulin injection practice in individuals with type 2 diabetes mellitus. This study was a quantitative research design with a cross-sectional approach using a questionnaire distributed to 32 respondents. The research was held at Club Prolanis Manado. Descriptive data analysis was conducted to describe the research variables. The findings showed that 100% of the respondents adhered well to insulin injections (Auto compliance > 80%), most respondents do not prime to check insulin flow and expel air before injecting insulin (78.1%), most respondents rotate the injection locations (75%), most respondents do not experience lipodystrophy (87.5%), more than half of the respondents experienced pain (53.1%), most of the respondents did not experience insulin leakage (81.2%), more than half of the respondents pinched during injection (56.2%), most of the respondents waited 10 seconds before removing the needle (75%). Skills and adherence in injecting insulin must be improved through continuous education and evaluation to achieve optimal glycemic control.